FUNGSI KESENIAN RONGGENG, RONGGENG NAK MUDO PINANG SARUMPUN DI NAGARI SIMPANG - Zalmesi Zulmar; Lisna Sandora (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2026)
Ronggeng is one of the traditional performing arts that plays an important role in the socio-cultural life of the community in Pasaman Regency, West Sumatra. This study aims to analyze the functions of Ronggeng Nak Mudo Pinang Sarumpun within the social and cultural practices of the Nagari Simpang community. A qualitative approach was employed through in-depth interviews, participant observation, and documentation involving ronggeng performers and community leaders. The findings reveal that ronggeng functions not only as entertainment but also as a medium for social cohesion, cultural communication, customary ceremonies, and the transmission of local values through poetic performances (pantun). From a functionalist perspective, ronggeng contributes to maintaining social integration and reinforcing collective identity, while its historical development reflects a process of cultural acculturation that has shaped the distinctive characteristics of ronggeng in Pasaman. These findings demonstrate that the sustainability of Ronggeng Nak Mudo Pinang Sarumpun is closely related to its continuing social functions and cultural relevance within the local community.